Taking the bite out of culture: The impact of task structure and task type on overcoming impediments to cross‐cultural team performance. (6th June 2013) - Nouri, Rikki; Erez, Miriam; Rockstuhl, Thomas; Ang, Soon; Leshem‐Calif, Lee; Rafaeli, Anat; Salas, Eduardo; Gelfand, Michele J.
Summary Research on the effect of cultural diversity on team performance remains inconclusive. We propose to resolve the competing predictions of the information/decision making versus the social categorization theories by integrating two task‐related theories, the situational strength theory and the circumplex model of group tasks. We propose that high task specificity enables similar interpretations and shared understanding among team members, which is needed for effective "execute" (convergent) tasks, is characterized by team cooperation and interdependence. Low task specificity, in contrast, is beneficial for "generate" (creative) tasks, because it does not place constraints on generating original ideas and does not require tight coordination among the team members. We tested the effects of situational strength and task type on the relationship between cultural diversity and team performance in two experiments with 86 and 96 dyads in the first and second experiments, respectively. In both experiments, heterogeneous (Israeli–Singaporean) and homogeneous dyads (Israeli–Israeli and Singaporean–Singaporean) worked under low or high task specificity. In Study 1, dyads performed convergent execution tasks, and in Study 2, they performed creative idea‐generation tasks. The impediment of multiculturalism was reduced in execute (convergent) tasks under high task specificity and in generate (divergent) tasks under low task specificity. Copyright © 2013 John Wiley & Sons, Ltd.